The Effect of Diabetes Mellitus Gymnastics Movement on Decreasing Current Blood Pressure Levels (GDS) in the Elderly - Setyawan, Bambang; Febriyona, Rona; Ilham, Rosmin (Bantayang Omni Cendekia, 2024)
Background: Diabetes mellitus is a disease with increased levels of sugar (glucose) in the body, there is a therapy for diabetes, namely diabetes mellitus gymnastics therapy Objective: The purpose of the study was to determine the effect of diabetes mellitus gymnastics movements on reducing blood pressure levels during (GDS) in the elderly Methods: Research design using pre-experimental methods with a one-group pre-post test design approach Results: The results showed an average blood sugar level when not controlled as much as 9 before being given exercise and blood sugar levels when controlled as many as 8 people after being given diabetic exercise, the results of data analysis showed a value of pValue = 0.040<0.05. Conclusion: Conclusion there is an influence of diabetes mellitus gymnastics movements on reducing current blood gulah levels (GDS) in the elderly at the Mootilango Health Center. Advice for the elderly to remain diligent in controlling blood sugar in health facilities.